In-situ electrochemical construction method of solid-state battery composite interface layer and battery

CN122992183APending Publication Date: 2026-10-27ZHEJIANG QIANMO NEW MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611247426.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-18
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]本发明针对现有固态电池负极界面层结构单一、无法同时满足柔顺贴合与机械强度要求的问题,提供一种通过两种不同电化学聚合起始电位的单体在首次充电过程中分步聚合,从而原位形成梯度结构或双层结构复合界面层的方法,以及包含该界面层的固态电池

Benefits of technology

本发明通过功能梯度设计,兼顾界面适配性与稳定性。依靠单体还原电位的天然差异,充电过程中自发形成内层柔韧、外层刚硬的梯度结构,紧贴负极的内层由低模量柔性聚合物构成,与负极表面结合力强,可自适应充放电过程中负极的体积膨胀与收缩,避免界面剥离与微裂纹产生;靠近固态电解质的外层由高模量刚性聚合物构成,可有效抑制锂枝晶穿刺,同时阻隔负极与固态电解质的直接接触,抑制界面副反应与电解质还原分解。本发明通过原位电化学聚合,界面结合强度高,聚合反应由负极表面的电子转移直接触发,聚合物链可与负极表面的活性位点形成共价键与离子键作用,同时与固态电解质表面形成紧密的离子键合,界面结合强度远高于物理涂覆的预构筑聚合物层,可耐受长期循环过程中的界面应力,避免界面脱离导致的阻抗飙升。通过引入含呋喃与马来酰亚胺基团的Diels-Alder动态交联单体,可将动态共价键接入聚合物网络中;当界面因体积应力产生微裂纹时,在温和温度条件下即可通过动态键的交换实现界面结构与离子传导性能的自修复,进一步提升电池在苛刻工况下的循环寿命与可靠性。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a kind of in-situ electrochemical construction methods of solid-state battery composite interface layer and battery.The method comprises: preparation includes at least two cathode reduction polymerization monomer precursor solution, the monomer has different electrochemical reduction onset potential, also includes lithium salt;The precursor solution is applied to solid-state electrolyte or negative electrode surface;Assemble battery and carry out first charge, with polymerization reaction front advances to solid-state electrolyte side, first monomer is preferentially polymerized at higher potential to form the inner layer in contact with negative electrode, second monomer is polymerized at lower potential to form the outer layer in contact with solid-state electrolyte, thereby forming the composite interface layer of gradient structure or double-layer structure in-situ at negative electrode and solid-state electrolyte interface.The application utilizes the reduction polymerization potential difference of different monomers, spontaneously forms the interface layer with performance gradually changing along the thickness direction in battery, inner layer is flexible to adapt volume change, outer layer is rigid to inhibit lithium dendrite, significantly reduces interface impedance, improves cycle life and reliability, and process is compatible with existing battery production line.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of solid-state lithium battery technology, specifically relating to a method for forming a composite interface layer with a gradient structure in situ at the interface of negative electrode / solid electrolyte by electrochemical triggering, and a solid-state battery containing the interface layer. Background Technology

[0002] Solid-state batteries use non-flammable solid electrolytes instead of liquid electrolytes, fundamentally improving battery safety. However, the rigid solid-solid contact between the solid electrolyte and the electrodes leads to a series of serious interface problems: poor physical contact results in high interfacial impedance; volume changes in electrode materials during charging and discharging (such as silicon expansion, lithium deposition / dissolution) can easily cause cracks or even detachment at the interface; and poor chemical / electrochemical compatibility can easily lead to persistent interfacial side reactions.

[0003] To address the aforementioned issues, existing technologies, such as CN110676510A, disclose a method for forming an interface modification layer by initiating the polymerization of alkenyl functionalized ionic liquid monomers using ultraviolet light. This method prepolymerizes the monomers using external ultraviolet light before battery assembly, forming a fixed polymer layer. However, this pre-construction method has inherent drawbacks: the prepolymerized layer cannot adapt to dynamic volume changes during subsequent electrochemical cycling; it lacks self-healing capabilities; and the interface layer has a homogeneous structure, making it difficult to simultaneously meet the requirements of flexible adhesion to the negative electrode and rigid compatibility with the solid electrolyte.

[0004] Another approach to improvement is to use electrochemically triggered in-situ polymerization to form an interface layer. However, this usually only uses a single monomer, resulting in a single interface layer with limited performance. It is difficult to simultaneously meet the dual requirements of high adhesion, low modulus to adapt to volume changes, and high mechanical strength to suppress lithium dendrites.

[0005] Therefore, there is an urgent need to develop a method that can form gradient or bilayer interface layers in situ, so that the interface layers have gradually varying composition and properties in different thickness directions, thereby solving the problems of volume adaptability and interface stability at the same time. Summary of the Invention

[0006] This invention addresses the problem that existing solid-state batteries have a single negative electrode interface layer structure that cannot simultaneously meet the requirements of flexible adhesion and mechanical strength. It provides a method for forming a gradient structure or bilayer composite interface layer in situ by stepwise polymerization of monomers with two different electrochemical polymerization initiation potentials during the first charge process, as well as a solid-state battery containing this interface layer.

[0007] To achieve the above objectives, the present invention provides an in-situ electrochemical construction method for a composite interface layer in a solid-state battery, comprising the following steps: S1. Prepare a precursor solution containing at least two electrochemically polymerizable monomers, said monomers having different electrochemical polymerization initiation potentials, said precursor solution further comprising a lithium salt; S2. The precursor solution is applied to the surface of a solid electrolyte or the surface of a negative electrode material to form a precursor layer; S3. Assemble the battery and perform the first step-by-step formation charge. As charging proceeds, the first monomer with a higher reduction initiation potential preferentially undergoes electrochemical reduction polymerization at the interface between the negative electrode and the precursor layer, forming an inner first polymer network in contact with the negative electrode. As the polymerization reaction front advances towards the solid electrolyte side, the second monomer with a lower reduction initiation potential undergoes electrochemical reduction polymerization on the side of the precursor layer closer to the solid electrolyte, forming an outer second polymer network in contact with the solid electrolyte. Thus, a composite interface layer with a gradient structure is formed in situ at the interface between the negative electrode and the solid electrolyte.

[0008] Furthermore, the electrochemical polymerization initiation potential of the first monomer is 1.5 V ~ 2.5 V (vs. Li). + / Li), the electrochemical polymerization initiation potential of the second monomer is 0.3 V ~ 1.2 V (vs. Li + / Li).

[0009] Furthermore, the first monomer is a monofunctional vinylimidazolium ionic liquid monomer, which forms a low-modulus flexible polymer network after polymerization; the second monomer is a multifunctional vinylimidazolium ionic liquid monomer or an aryl-substituted vinylimidazolium ionic liquid monomer, which forms a high-modulus rigid polymer network after polymerization. The first monomer, being a monofunctional vinylimidazolium ionic liquid, exhibits high reducing activity due to the strong electron-withdrawing effect of the imidazole cation, which reduces the electron cloud density of the vinyl double bond at 1.5–2.5 V vs. Li. + At a potential of / Li, electrons can be gained on the negative electrode surface to generate free radical anions, initiating double bond polymerization. The polymerized product has good chain segment flexibility, low elastic modulus, and strong binding force with the active sites on the negative electrode surface, which can adapt to the volume deformation of the negative electrode during charging and discharging. The second monomer is an aryl-substituted or multifunctional vinylimidazolium ionic liquid. The steric hindrance and conjugation effect of the aromatic ring, or the multifunctional cross-linked structure, shifts its reduction initiation potential negatively to 0.3~1.2 V vs. Li. + / Li; the polymer product has a high degree of cross-linking, strong rigidity, and high elastic modulus, which can effectively block lithium dendrite penetration, while also preventing direct contact between the solid electrolyte and the negative electrode and suppressing interfacial side reactions.

[0010] Further, the first monomer is 1-vinyl-3-methylimidazolium thiocyanate, 1-vinyl-3-ethylimidazolium thiocyanate, 1-vinyl-3-methylimidazolium hydrogen sulfate, 1-vinyl-3-ethylimidazolium hydrogen sulfate, 1-vinyl-3-methylimidazolium acetate, 1-vinyl-3-ethylimidazolium acetate, 1-vinyl-3-methylimidazolium nitrate, 1-vinyl-3-ethylimidazolium nitrate, 1-vinyl-3-methylimidazolium difluorosulfonylimide salt, 1-vinyl-3-ethylimidazolium difluorosulfonylimide salt, 1-vinyl-3-methylimidazolium difluoromethanesulfonylimide salt, 1-vinyl-3-ethylimidazolium difluoromethanesulfonylimide salt, 1-vinyl-3-methylimidazolium trifluoromethanesulfonate, 1-vinyl-3-ethylimidazolium trifluoromethanesulfonate, 1-vinyl-3-methylimidazolium tetrafluoroborate, One or more of the following monomers are preferred: 1-vinyl-3-ethylimidazolium tetrafluoroborate, 1-vinyl-3-methylimidazolium dicyandiamide, 1-vinyl-3-ethylimidazolium dicyandiamide, 1-propanesulfonic-3-vinylimidazolium iodide, 1-propanesulfonic-3-vinylimidazolium bromide, 1-propanesulfonic-3-vinylimidazolium bis(trifluoromethanesulfonyl)imide, 1-propanesulfonic-3-vinylimidazolium hydrogen sulfate, 1-butanesulfonic-3-vinylimidazolium bis(trifluoromethanesulfonyl)imide, 1-butanesulfonic-3-vinylimidazolium hydrogen sulfate, and polymerizable ionic liquids with longer side chains; the second monomer is 1-benzyl-3-vinylimidazolium bis(trifluoromethanesulfonyl)imide or 1,3-divinylimidazolium bis(trifluoromethanesulfonyl)imide, preferably 1-benzyl- 3-Vinylimidazolium bis(trifluoromethanesulfonyl)imide salt.

[0011] Furthermore, the lithium salt is selected from at least one of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and lithium bis(fluorosulfonyl)imide (LiFSI). The organic solvent is selected from at least one of ethyl methyl carbonate, dimethyl carbonate, N-methylpyrrolidone, and acetonitrile.

[0012] Furthermore, the mass ratio of the first monomer to the second monomer in the precursor solution is 1:3 to 3:1.

[0013] Furthermore, the thickness of the in-situ formed composite interface layer is 20 nm to 2 μm, wherein the inner layer accounts for 30% to 70% of the thickness, and the elastic modulus of the inner layer is lower than that of the outer layer.

[0014] Furthermore, in step S1, 0.1-1 wt% of a Diels-Alder dynamic crosslinking monomer containing furan and maleimide groups is added to the precursor solution; the Diels-Alder dynamic crosslinking monomer is grafted into the polymer network through vinyl groups to impart self-healing properties to the interface layer; specifically, it can be a furan derivative monomer and a maleimide derivative containing polymerizable vinyl groups; the furan monomer can be one or more of 2-hydroxymethylfuran, 2-formylfuran, 2-furanmethylamine, 2-furancarboxylic acid, 2-furancarboxylic acid vinyl ester or 2-furancarboxylate; the polymerizable vinyl maleimide derivative monomer can be one or more of N-isopropyl-N'-vinylmaleimide, N-vinylmaleimide, N-(4-vinylbenzyl)maleimide.

[0015] Furthermore, the initial stepped formation charging in step S3 employs a two-electrode constant current and constant voltage process, specifically including: Charge the battery to the first preset full cell voltage with a small constant current of 0.02C~0.1C, maintain the constant voltage for 10~60 min, and trigger the full polymerization of the first monomer. Continue constant current charging to the second preset full cell voltage, maintain constant voltage for 10~60 min, and trigger full polymerization of the second monomer; Finally, charge the battery to its rated cutoff voltage using the standard charging procedure.

[0016] The present invention also provides a solid-state battery, including a positive electrode, a negative electrode, and a solid electrolyte located between the positive electrode and the negative electrode; and the negative electrode and the solid electrolyte have a composite interface layer with a gradient structure formed in situ by the above method.

[0017] Furthermore, the solid electrolyte is a sulfide solid electrolyte or an oxide solid electrolyte; the negative electrode is a silicon-based negative electrode, a graphite negative electrode, a lithium metal negative electrode, or a lithium alloy negative electrode.

[0018] The beneficial effects of this invention are: This invention employs a functional gradient design to balance interface adaptability and stability. Utilizing the inherent differences in monomer reduction potentials, a gradient structure spontaneously forms during charging: a flexible inner layer and a rigid outer layer. The inner layer, closely adhering to the negative electrode, is composed of a low-modulus flexible polymer, exhibiting strong adhesion to the negative electrode surface. This allows it to adapt to the volume expansion and contraction of the negative electrode during charging and discharging, preventing interface delamination and microcrack formation. The outer layer, close to the solid electrolyte, is composed of a high-modulus rigid polymer, effectively suppressing lithium dendrite penetration while preventing direct contact between the negative electrode and the solid electrolyte, thus inhibiting interfacial side reactions and electrolyte reduction and decomposition. This invention utilizes in-situ electrochemical polymerization, resulting in high interfacial bonding strength. The polymerization reaction is directly triggered by electron transfer from the negative electrode surface. The polymer chains form covalent and ionic bonds with the active sites on the negative electrode surface, while simultaneously forming tight ionic bonds with the solid electrolyte surface. The interfacial bonding strength is significantly higher than that of physically coated pre-constructed polymer layers, allowing it to withstand interfacial stress during long-term cycling and preventing impedance spikes caused by interfacial delamination. By introducing Diels-Alder dynamic crosslinking monomers containing furan and maleimide groups, dynamic covalent bonds can be incorporated into the polymer network. When microcracks are generated at the interface due to volume stress, the interface structure and ion conduction performance can be self-repaired through the exchange of dynamic bonds under mild temperature conditions, further improving the cycle life and reliability of the battery under harsh conditions. Detailed Implementation

[0019] The present invention will be described in detail below with reference to embodiments, but the scope of protection of the present invention is not limited thereto.

[0020] This invention provides an in-situ electrochemical construction method for a composite interface layer in solid-state batteries, comprising the following steps: S1. Preparation of precursor solution: A precursor solution containing at least two cathodic reducible polymerizable monomers, said monomers having different electrochemical reduction initiation potentials, is prepared, and also includes a lithium salt and an organic solvent.

[0021] Among them, the electrochemical reduction initiation potential of the first monomer is relatively high, at 1.5 V ~ 2.5 V vs. Li. + / Li, preferably a monofunctional vinylimidazolium ionic liquid monomer, forms a low-modulus flexible polymer network after polymerization; the second monomer has a low electrochemical reduction onset potential, 0.3 V ~ 1.2 V vs. Li. + / Li, preferably a multifunctional vinylimidazolium ionic liquid monomer or an aryl-substituted vinylimidazolium ionic liquid monomer, forms a high-modulus rigid polymer network after polymerization.

[0022] The lithium salt is selected from at least one of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and lithium bis(fluorosulfonyl)imide (LiFSI). The organic solvent is selected from at least one of methyl ethyl carbonate, dimethyl carbonate, N-methylpyrrolidone, and acetonitrile.

[0023] S2. Application of precursor layer: The precursor solution is applied to the surface of a solid electrolyte sheet or a negative electrode material by coating, spraying or dipping, and then dried in an inert atmosphere to remove the solvent, forming a precursor layer with a thickness of 100 nm to 5 μm.

[0024] S3. Battery assembly and in-situ composite interface formation: The treated solid electrolyte sheet is assembled with the negative and positive electrodes to form a battery. The assembled battery undergoes its first charge formation. As charging progresses, the negative electrode potential gradually decreases: when the negative electrode potential drops to the reduction initiation potential of the first monomer, the first monomer preferentially undergoes electrochemical reduction polymerization on the negative electrode surface, forming an inner flexible polymer network tightly bonded to the negative electrode; charging continues until the negative electrode potential drops to the reduction initiation potential of the second monomer, where the second monomer undergoes electrochemical reduction polymerization on the already formed inner layer surface, near the solid electrolyte, forming an outer rigid polymer network. A gradient transition region exists between the two layers, with interpenetrating molecular chains, ultimately forming a composite interface layer with a gradient structure in situ at the interface between the negative electrode and the solid electrolyte.

[0025] The total thickness of the in-situ formed composite interface layer is 20 nm to 2 μm, with the inner layer accounting for 30% to 70% of the thickness. The inner layer has a low elastic modulus (0.1 to 1 GPa), excellent flexibility and interfacial adhesion, and can adapt to the volume changes during the charging and discharging process of the negative electrode; the outer layer has a high elastic modulus (1 to 5 GPa), high mechanical strength, and can suppress lithium dendrite growth and maintain stable interfacial contact with the solid electrolyte.

[0026] Preferably, the inner polymer network of the composite interface layer contains in-situ dispersed inorganic nanoparticles such as LiF, Li2S, and Li3P generated by the reduction of lithium salt and solid electrolyte at the interface, forming an organic-inorganic composite structure, which can further enhance the ion conductivity and interface stability of the interface layer.

[0027] Example 1: (1) Preparation of precursor solution: In an argon glove box, 0.3 g of 1-vinyl-3-ethylimidazolium bis(trifluoromethanesulfonyl)imine salt (VEIM-TFSI), 0.2 g of 1-benzyl-3-vinylimidazolium bis(trifluoromethanesulfonyl)imine salt (BVIM-TFSI), and 0.1 g of LiTFSI were dissolved in 5 g of methyl ethyl carbonate and stirred until homogeneous to obtain a pale yellow transparent precursor solution.

[0028] (2) Application of precursor layer: The above solution was uniformly coated onto the surface of a Li6PS5Cl sulfide solid electrolyte disc with a diameter of 12 mm and a thickness of approximately 0.5 mm using a slit coating method. The disc was then dried at 60°C for 2 hours in a glove box to remove the solvent, forming a precursor film with a thickness of approximately 1.2 μm.

[0029] (3) Battery assembly and composite interface formation: Using NCM811 as the positive electrode and graphite as the negative electrode, a 2025-type two-electrode coin cell was assembled with the aforementioned treated electrolyte sheet. The first step-by-step formation charge was performed at 25°C. ① Charge the battery at a constant current of 0.05C until the full cell voltage is 2.2 V, and maintain the constant voltage for 30 min. During this stage, the electron transfer rate at the interface is controlled by a small current. VEIM-TFSI with a higher reduction potential preferentially obtains electrons on the surface of the negative electrode and polymerizes to form a flexible inner layer that is closely attached to the negative electrode. ② Continue charging at a constant current of 0.05C until the full cell voltage is 3.4 V, and maintain the constant voltage for 30 min; as the inner layer polymer is formed, the polymerization reaction front moves towards the solid electrolyte side, the effective interface potential is further reduced, triggering the polymerization of BVIM-TFSI with a lower reduction potential, forming a rigid outer layer close to the solid electrolyte; ③ Subsequently, the cell was charged at a constant current of 0.1C to a full cell voltage of 4.2 V, completing the formation process. Finally, a gradient composite interface layer with a total thickness of approximately 800 nm was formed, with an inner layer thickness of approximately 400 nm and an outer layer thickness of approximately 400 nm. There is a gradient transition region between the two layers where molecular chains interpenetrate.

[0030] (4) Performance testing: Interface impedance: The interface impedance after the first cycle is 22 Ω·cm 2 After 300 cycles, the Ω·cm is 48. 2 .

[0031] Cycling performance: At a 0.5C rate, the capacity retention rate is 89.2% after 300 cycles.

[0032] Self-healing test: After 100 cycles, a small impact was applied to the battery to introduce microcracks at the interface, and the capacity temporarily decreased by 7.5%; after being left to stand at 60°C for 12 hours, the capacity recovered to 98.3% of the original value.

[0033] Modulus testing: The average modulus of the inner layer was 0.45 GPa and the average modulus of the outer layer was 2.8 GPa, as measured by nanoindentation.

[0034] Example 2: Precursor solution: Dissolve 0.25 g VEIM-TFSI, 0.25 g BVIM-TFSII, and 0.1 g LiFSI in 5 g methyl ethyl carbonate and stir until homogeneous.

[0035] Operation: Initial step-by-step transformation procedure: ① Charge the battery at a constant current of 0.05C to a full cell voltage of 2.1V, maintain the constant voltage for 20 minutes, and trigger VEIM-TFSI polymerization to form the inner layer; ② Continue constant current charging until the full cell voltage reaches 3.3 V, maintain constant voltage for 20 min to trigger BVIM-TFSI polymerization to form the outer layer; ③ Then charge normally until the full battery voltage is 4.2 V.

[0036] Effect: Battery at 0.5 mA / cm 2 The cycle life exceeds 1200 hours. The full cell retains 86.5% capacity after 200 cycles at 0.5C.

[0037] Example 3: Improvement of precursor solution: In the precursor solution of Example 1, an additional 0.5 wt% of Diels-Alder dynamic crosslinking monomer combination was added, specifically a furan derivative containing polymerizable vinyl groups and a maleimide derivative containing polymerizable vinyl groups. The molar ratio of 2-vinyl furanoate and N-isopropyl-N'-vinyl maleimide was 1:1. The remaining raw materials, preparation process and testing conditions were the same as in Example 1.

[0038] Results: After local damage, the formed interface layer can achieve faster and more complete covalent bond network repair at a temperature of 60°C, further improving the durability of the interface under harsh conditions.

[0039] Comparative Example 1 Only VEIM-TFSI (0.5 g) was used, and everything else was the same as in Example 1. The resulting interface layer was a homogeneous structure.

[0040] Result: Initial interfacial impedance 35 Ω·cm 2 After 150 cycles, the Ω·cm increased to 189 Ω·cm. 2 After 300 cycles, the capacity retention rate was only 72%.

[0041] Comparative Example 2: The prepolymerized PEO-LiTFSI gel electrolyte was directly pressed onto the surface of the Li6PS5Cl electrolyte sheet, and then assembled into a battery with the same graphite anode and NCM811 cathode, without performing an in-situ electrochemical polymerization process.

[0042] Performance and Issues: The initial interface impedance is 89 Ω·cm 2 It is higher than that of Example 1.

[0043] After 100 cycles, the impedance increased sharply to 589 Ω·cm. 2 .

[0044] After 150 cycles, the capacity retention rate was only 70%. Upon disassembly, it was found that there were obvious gaps at the interface between the PEO layer and the sulfide electrolyte.

[0045] Conclusion: The pre-constructed physical bonding interface cannot adapt to cyclic stress and is prone to detachment.

[0046] Comparative Example 3: VEIM-TFSI, BVIM-TFSI and LiTFSI were mixed in the same proportion as in Example 1, and an initiator was added to form a homogeneous polymer film through thermal initiation. The film was then pressed onto the surface of the Li6PS5Cl electrolyte and the battery was assembled. In-situ stepwise electrochemical polymerization process was not used.

[0047] Performance and Issues: The interface layer is a homogeneous, gradient-free structure with an initial interface impedance of 56 Ω·cm. 2 After 200 cycles, obvious signs of lithium dendrite infiltration appeared, and the interfacial impedance soared to 320 Ω·cm. 2 The capacity retention rate was only 68%.

[0048] Conclusion: Non-in-situ homogeneous polymer layers cannot achieve functional partitioning with a flexible inner layer and a rigid outer layer. They are difficult to adapt to changes in the volume of the negative electrode and cannot effectively block lithium dendrites. Their performance is far lower than that of in-situ gradient structure interface layers.

[0049] The above are merely preferred embodiments of the present invention, and only specifically describe the technical principles of the present invention. These descriptions are only for explaining the principles of the present invention and should not be construed as limiting the scope of protection of the present invention in any way. Based on this explanation, any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention, as well as other specific embodiments of the present invention that can be conceived by those skilled in the art without creative effort, should be included within the scope of protection of the present invention.

Claims

1. An in-situ electrochemical construction method for a composite interface layer in a solid-state battery, characterized in that, Includes the following steps: S1. Prepare a precursor solution containing at least two electrochemically polymerizable monomers, said monomers having different electrochemical polymerization initiation potentials, said precursor solution further comprising a lithium salt; S2. The precursor solution is applied to the surface of a solid electrolyte or the surface of a negative electrode material to form a precursor layer; S3. Assemble the battery and perform the first step-by-step formation charge. As charging proceeds, the first monomer with a higher reduction initiation potential preferentially undergoes electrochemical reduction polymerization at the interface between the negative electrode and the precursor layer, forming an inner first polymer network in contact with the negative electrode. As the polymerization reaction front advances towards the solid electrolyte side, the second monomer with a lower reduction initiation potential undergoes electrochemical reduction polymerization on the side of the precursor layer closer to the solid electrolyte, forming an outer second polymer network in contact with the solid electrolyte. Thus, a composite interface layer with a gradient structure is formed in situ at the interface between the negative electrode and the solid electrolyte.

2. The method according to claim 1, characterized in that, The electrochemical polymerization initiation potential of the first monomer is 1.5 V ~ 2.5 V (vs. Li). + / Li), the electrochemical polymerization initiation potential of the second monomer is 0.3 V ~ 1.2 V (vs. Li + / Li).

3. The method according to claim 1, characterized in that, The first monomer is a monofunctional vinylimidazolium ionic liquid monomer, which forms a low-modulus flexible polymer network after polymerization; the second monomer is a polyfunctional vinylimidazolium ionic liquid monomer or an aryl-substituted vinylimidazolium ionic liquid monomer, which forms a high-modulus rigid polymer network after polymerization.

4. The method according to claim 3, characterized in that, The first monomer is 1-vinyl-3-ethylimidazolium bis(trifluoromethanesulfonyl)imine salt, and the second monomer is 1-benzyl-3-vinylimidazolium bis(trifluoromethanesulfonyl)imine salt or 1,3-divinylimidazolium bis(trifluoromethanesulfonyl)imine salt.

5. The method according to claim 1, characterized in that, The mass ratio of the first monomer to the second monomer in the precursor solution is 1:3 to 3:

1.

6. The method according to claim 1, characterized in that, The thickness of the in-situ formed interface layer is 20 nm to 2 μm, of which the inner layer accounts for 30% to 70% of the thickness, and the elastic modulus of the inner layer is lower than that of the outer layer.

7. The method according to claim 1, characterized in that, In step S1, 0.1-1 wt% of a Diels-Alder dynamic crosslinking monomer containing furan and maleimide groups is added to the precursor solution.

8. The method according to claim 1, characterized in that, The initial stepped formation charging in step S3 employs a two-electrode constant current and constant voltage process, specifically including: Charge the battery to the first preset full cell voltage with a small constant current of 0.02C~0.1C, maintain the constant voltage for 10~60 min, and trigger the full polymerization of the first monomer. Continue constant current charging to the second preset full cell voltage, maintain constant voltage for 10~60 min, and trigger full polymerization of the second monomer; Finally, charge the battery to its rated cutoff voltage using the standard charging procedure.

9. A solid-state battery, characterized in that, It includes a positive electrode, a negative electrode, and a solid electrolyte located between the positive electrode and the negative electrode; and the negative electrode and the solid electrolyte have a composite interface layer with a gradient structure formed in situ by the method of any one of claims 1-8.

10. The solid-state battery according to claim 9, characterized in that, The solid electrolyte is a sulfide solid electrolyte or an oxide solid electrolyte; the negative electrode is a silicon-based negative electrode, a graphite negative electrode, a lithium metal negative electrode, or a lithium alloy negative electrode.

Citation Information

Patent Citations

  • Modification layer for solid-state lithium battery electrode / solid electrolyte interface and preparation method thereof and application

    CN110676510A